A comparison of Volatile Organic Compounds (VOCs) and the Concept of Gandha with special reference to Balagraha - Lekshmi , M K; Nair, Revathi S (International Research Journal of Ayurveda & Yoga, 2022)
The ancient science of Ayurveda has many unique concepts regarding the creation of the living, health issues, diseases and their treatment. These are distinctive and have the scope to incorporate modern development into them. During the trying times of the recent pandemic, there has been the development of sensors for detecting VOCs (volatile organic compounds) produced by COVID-infected individuals which helped to diagnose the disease swiftly to minimize its spread. The interaction between pathogenic viruses in respiratory tract infection and the body’s microenvironment produces distinctive volatile organic compounds (VOCs). VOCs are gaseous molecules released as a product of metabolic processes in the body whose composition changes directly as a result of pathologic processes, such as an infection. This concept of different body odours in physiological and pathological conditions has been mentioned in Ayurveda thoroughly, especially in the context of Balagraha (which can be correlated to various infectious diseases). This shows the science’s proficiency to be way ahead of its time. Thus, the incorporation of such distinctive ayurvedic concepts will help in the comprehensive development of the medical sciences.